PENERAPAN METODA NUMERIK ELEMEN HINGGA PADA MODEL HIDRODINAMIKA TIGA DIMENSI - Bekti Santoso (NIM : 25097020), Purwanto
Abstrak : We need three-dimensional modeling whenever the information given by two-dimensional modeling is not enough. There are some cases where we need three-dimensional modeling such as density differences (stratified flow) and water circulation because of temperature differences. Flow in bending channel also produces an important three-dimensional structure. The solution of non-linear hydrodynamics modeling we used here is based on shallow water wave equation formed by rearranging primitive three dimensional shallow water equations to get the elevation. The horizontal and vertical velocities are come from the transformed momentum and continuity equation in (x, y, coordinate system. Discretization of the governing equation is Galerldn Finite Element Method that using simple linear hexagonal element formed by linear triangular element on horizontal and linear variation in vertical. A semi-implicit time stepping algorithm allows the solutions for elevation and velocity to be uncoupled during each time step. Model is applied and verified for simple cases and cases that have analytical solution.